Evaluating EFL textbooks for vocational high schools in Indonesia: A corpus-informed and lexile-based model - Diana Omega Santi; Ignatius Tri Endarto (Studies in English Language and Education, 2024)
Even though textbooks play an integral role in EFL teaching and learning processes, evaluation of English textbooks for vocational high schools in the Indonesian context and their relevancy to the targeted proficiency was still rare. This study identified text difficulty levels and English vocabulary profiles of a set of digital English coursebooks for vocational high schools in Indonesia. It also analyzed how text difficulty levels and vocabulary profiles correspond with the targeted proficiency level of vocational high school graduates. A corpus-informed and Lexile-based model was employed as the design of this research. Lexile framework was employed to measure text difficulty, while corpus information was utilized to determine the vocabulary profiles of the selected textbooks. Three tools were used to analyze the data quantitatively, namely Lexile Text Analyzer Professional, LancsBox, and English Vocabulary Profile in Text Inspector. This study found that the approximate text difficulty of reading passages in the coursebooks for grades 10 and 12 is slightly higher than the expected language proficiency level for vocational high school graduates. On the other hand, the approximate text difficulty of reading passages in the coursebook for grade 11 is slightly lower. However, in terms of vocabulary profiles, the three books emphasize the target vocabulary at the expected level (B1), as suggested by the Directorate of Vocational High School Development. In addition to those findings, it is important that teachers consider other factors outside the scope of this research, such as learners proficiency levels and interests or other qualitative data about the books, to determine whether the coursebooks are appropriate for their classes.